A NASICON structure lithium ion solid electrolyte material and its preparation method and application

By using NASICON structure lithium-ion solid electrolyte material in lithium-ion batteries, containing stable zirconium and silicon elements, and using high-temperature solid phase method, the safety hazards of liquid electrolytes in lithium-ion batteries and the low efficiency of traditional solid electrolyte preparation Problem, achieving more stable and efficient battery performance.

CN114388880BActive Publication Date: 2024-12-31LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210061299.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-19
Publication Date
2024-12-31
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

The liquid electrolyte used in existing lithium-ion batteries has safety risks, such as internal short circuit, liquid leakage, combustion and even explosion. The traditional LiTi2(PO4)3 solid electrolyte restricts its application due to the activeness of titanium, and the preparation of replacement materials Inefficient.

Method used

The NASICON structure lithium-ion solid electrolyte material contains stable zirconium and silicon elements. It is prepared by high-temperature solid phase method. The material has stable chemical properties and good compatibility with positive and negative electrode materials. The preparation method is simple and easy to be produced in industrial use.

Benefits of technology

In lithium-ion batteries, the stability and safety of electrolytes are improved, the reaction with positive and negative electrode materials is avoided, and more efficient battery performance and production efficiency are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114388880B_ABST
    Figure CN114388880B_ABST
Patent Text Reader

Abstract

The present invention discloses a NASICON structure lithium ion solid electrolyte material and a preparation method and application thereof. The chemical general formula of the NASICON structure lithium ion solid electrolyte material is Li (x‑4y+9) Zr y Si x P (3‑x) O 12 ; 0<x<3, 1≤y≤2. The NASICON structure lithium ion solid electrolyte material provided by the present invention contains stable zirconium and silicon elements. Compared with other solid electrolytes, when it is used as the electrolyte layer in a lithium ion battery, its chemical properties are more stable during the battery charging and discharging process. It has the advantages of not reacting with the positive and negative electrode materials and having good compatibility with the positive and negative electrode materials. The preparation method of the NASICON structure lithium ion solid electrolyte material of the present invention is a high-temperature solid phase method. The preparation method is simple, low in cost, high in safety, and easy to realize industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a NASICON structure lithium ion solid electrolyte material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high voltage, low self-discharge rate, and high energy density, so lithium-ion batteries are gradually replacing traditional batteries and expanding their application areas. However, with the continuous improvement of the energy density of lithium-ion batteries and the large-scale energy storage modules, the safety risks of lithium-ion batteries have always been the primary problem that researchers have to solve. Electrolyte is one of the key components of high-energy secondary lithium batteries. Although electrode materials are a prerequisite for determining the energy density of secondary lithium batteries, the energy density is related to its reaction kinetics, cycle stability, and safety, which are all directly related to the electrolyte. At present, secondary lithium batteries mainly use liquid electrolytes, and secondary lithium batteries using liquid electrolytes have safety hazards such as internal short circuits, leakage, combustion, and even explosions. In order to solve the above problems, researchers have proposed the idea of ​​replacing traditional liquid organic electrolytes with solid electrolytes.

[0003] Solid electrolytes generally include two categories, the first category is inorganic solid electrolytes, and the second category is electrolytes composed of polymers, lithium salts and fillers. At present, the inorganic solid electrolytes that are studied more and have prospects are inorganic solid electrolytes, including perovskite type, NASICON type, LISICON type, Li3N and glassy solid electrolytes. Among them, NASICON type solid electrolytes have the advantages of good structural stability and high porosity, but the common LiTi2(PO4)3 solid electrolytes have defects such as instability to lithium and easy electronic conductivity due to the activity of titanium, which greatly limits its application in lithium batteries. The new solid electrolytes formed by replacing titanium with silicon and zirconium have the advantages of stable properties and high conductivity, but they are currently mainly prepared by substitution methods, with low production efficiency and complicated processes. Therefore, a simpler and more efficient preparation method is needed. Summary of the invention

[0004] The embodiment of the present invention provides a NASICON structure lithium ion solid electrolyte material and its preparation method and application. The NASICON structure lithium ion solid electrolyte material contains stable zirconium and silicon elements. Compared with other solid electrolytes, when it is used as an electrolyte layer in a lithium ion battery, its chemical properties are more stable during the battery charging and discharging process, and it has the advantages of not reacting with positive and negative electrode materials and having good compatibility with positive and negative electrode materials. The preparation method of the NASICON structure lithium ion solid electrolyte material provided by the present invention has the advantages of easy availability of raw materials, low cost, simple preparation method, and easy industrial mass production.

[0005] In a first aspect, an embodiment of the present invention provides a NASICON structure lithium ion solid electrolyte material, wherein the chemical formula of the NASICON structure lithium ion solid electrolyte material is Li (x-4y+9) Zr y Si x P (3-x) O 12 ;0<x<3,1≤y≤2.

[0006] In a second aspect, an embodiment of the present invention provides a method for preparing the NASICON structure lithium ion solid electrolyte material described in the first aspect, wherein the preparation method is a high temperature solid phase method, comprising:

[0007] Weigh the raw materials in proportion, and mix the raw materials evenly by dry mixing or wet mixing to obtain a mixed material;

[0008] placing the mixed material in a high temperature treatment device for heat treatment to obtain a precursor;

[0009] The precursor is subjected to graded crushing treatment to obtain NASICON structure lithium ion solid electrolyte material with a particle size between 500nm-50μm;

[0010] The chemical formula of the NASICON structure lithium ion solid electrolyte material is Li (x-4y+9) Zr y Si x P (3-x) O 12 , where 0<x<3, 1≤y≤2.

[0011] Preferably, the raw materials include: lithium-containing compounds, zirconium-containing compounds, silicon-containing compounds and phosphorus-containing compounds;

[0012] The lithium-containing compound includes: one or more of lithium carbonate, lithium hydroxide, lithium oxide or lithium phosphate; the particle size of the lithium-containing compound particles is between 20nm-50μm;

[0013] The zirconium-containing compound includes: one or more of zirconium oxide, zirconium hydroxide, zirconium silicate or zirconium hydrogen phosphate; the particle size of the zirconium-containing compound particles is between 20nm-50μm;

[0014] The silicon-containing compound includes: silicon dioxide and / or silicon monoxide; the particle size of the silicon-containing compound particles is between 20nm-50μm;

[0015] The phosphorus-containing compound comprises: one or more of lithium phosphate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphorus pentoxide; the particle size of the phosphorus-containing compound particles is between 20nm-50μm.

[0016] Preferably, the dry mixing comprises: mixing using a ball mill, mixing using a dual motion mixer, or mixing using a high-speed mixer;

[0017] The wet mixing includes: ball milling mixing, sand milling mixing or dispersion mixing.

[0018] Preferably, the heat treatment equipment includes: a box furnace, a tube furnace, a track kiln, a rotary kiln or a push plate kiln.

[0019] Preferably, the heat treatment comprises: heating to 900°C-1300°C at a heating rate of 0.5°C / min-12°C / min, keeping the temperature for 5 hours-30 hours, and then naturally cooling to room temperature.

[0020] Preferably, the equipment for graded crushing processing includes: a jaw crusher, a cone crusher, an impact crusher, a hammer crusher, a roller crusher, a flat air flow mill, a fluidized bed air flow mill, a circulating air flow mill, an impact crusher, an expansion crusher, a ball mill, a high-speed rotating projectile mill or a high-speed rotating impact mill.

[0021] In a third aspect, an embodiment of the present invention provides a diaphragm, wherein the diaphragm includes the NASICON structure lithium ion solid electrolyte material described in the first aspect.

[0022] In a fourth aspect, an embodiment of the present invention provides a lithium battery, wherein the lithium battery comprises the separator described in the third aspect.

[0023] The NASICON structure lithium ion solid electrolyte material provided by the present invention contains stable zirconium and silicon elements. Compared with other solid electrolytes, when it is used as an electrolyte layer in a lithium ion battery, its chemical properties are more stable during the battery charging and discharging process, and it has the advantages of not reacting with positive and negative electrode materials and having good compatibility with positive and negative electrode materials. The preparation method of the NASICON structure lithium ion solid electrolyte material provided by the embodiment of the present invention is a high-temperature solid phase method, which has the advantages of easy availability of raw materials, low cost, simple preparation method, and easy industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0025] Figure 1is a flow chart of a method for preparing a NASICON structure lithium ion solid electrolyte material provided by an embodiment of the present invention;

[0026] Figure 2 is an X-ray diffraction pattern (XRD) of the NASICON structure lithium ion solid electrolyte material provided in Example 1 of the present invention;

[0027] Figure 3 is a volume particle size distribution curve of the NASICON structure lithium ion solid electrolyte material provided in Example 1 of the present invention;

[0028] Figure 4 is an XRD diagram of the NASICON structure lithium ion solid electrolyte material provided in Example 2 of the present invention;

[0029] Figure 5 is a volume particle size distribution curve of the NASICON structure lithium ion solid electrolyte material provided in Example 2 of the present invention;

[0030] Figure 6 is an XRD diagram of the NASICON structure lithium ion solid electrolyte material provided in Example 3 of the present invention;

[0031] Figure 7 This is the volume particle size distribution curve of the NASICON structure lithium ion solid electrolyte material provided in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0033] The embodiment of the present invention provides a NASICON structure lithium ion solid electrolyte material, the chemical formula of the NASICON structure lithium ion solid electrolyte material is Li (x-4y+9) Zr y Si x P (3-x) O 12 ;0<x<3,1≤y≤2.

[0034] The embodiment of the present invention provides a method for preparing the NASICON structure lithium ion solid electrolyte material of the first aspect, the preparation method is a high temperature solid phase method, comprising:

[0035] Step 110, weighing raw materials in proportion, and mixing the raw materials uniformly by dry mixing or wet mixing to obtain a mixed material;

[0036] The raw materials include: lithium-containing compounds, zirconium-containing compounds, silicon-containing compounds and phosphorus-containing compounds;

[0037] In actual preparation, because a small amount of lithium and phosphorus volatilize during the high-temperature preparation process, lithium and phosphorus need to be slightly excessive in the actual raw material ratio selection, and the excess range is between 2% and 20%;

[0038] The lithium-containing compound includes: one or more of lithium carbonate, lithium hydroxide, lithium oxide or lithium phosphate; the particle size of the lithium-containing compound particles is between 20nm-50μm;

[0039] The zirconium-containing compound includes: one or more of zirconium oxide, zirconium hydroxide, zirconium silicate or zirconium hydrogen phosphate; the particle size of the zirconium-containing compound particles is between 20nm-50μm;

[0040] The silicon-containing compound includes: silicon dioxide and / or silicon monoxide; the particle size of the silicon-containing compound particles is between 20nm-50μm;

[0041] The phosphorus-containing compound includes: one or more of lithium phosphate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphorus pentoxide; the particle size of the phosphorus-containing compound particles is between 20nm-50μm;

[0042] Dry mixing includes: mixing using a ball mill, mixing using a dual motion mixer, or mixing using a high speed mixer;

[0043] Wet mixing includes: ball milling, sand milling or dispersion mixing.

[0044] Step 120, placing the mixed material in a high temperature treatment device for heat treatment to obtain a precursor;

[0045] The heat treatment equipment includes: a box furnace, a tube furnace, a track kiln, a rotary kiln or a push plate kiln.

[0046] The heat treatment includes: heating to 900°C-1300°C at a heating rate of 0.5°C / min-12°C / min, keeping the temperature for 5 hours-30 hours, and then naturally cooling to room temperature.

[0047] Step 130, subjecting the precursor to graded crushing treatment to obtain a NASICON structure lithium ion solid electrolyte material;

[0048] The equipment for graded crushing treatment includes: one of the following: jaw crusher, cone crusher, impact crusher, hammer crusher, roller crusher, flat air flow mill, fluidized bed air flow mill, circulating air flow mill, impact crusher, expansion crusher, ball mill, high-speed rotary projection mill or high-speed rotary impact mill;

[0049] The chemical formula of the prepared NASICON structure lithium-ion solid electrolyte material is Li (x-4y+9) Zr y Si x P (3-x) O 12 , where 0<x<3, 1≤y≤2.

[0050] An embodiment of the present invention provides a diaphragm, which includes the above-mentioned NASICON structure lithium ion solid electrolyte material. The diaphragm can be applied to lithium batteries.

[0051] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the NASICON structure lithium ion solid electrolyte material of the present invention are respectively described below with multiple specific examples.

[0052] Example 1

[0053] This embodiment provides a method for preparing a NASICON structure lithium-ion solid electrolyte material.

[0054] The specific steps are as follows:

[0055] 1.55 parts of lithium carbonate 5 μm powder, 2 parts of zirconium dioxide 3 μm powder, 2 parts of silicon dioxide powder and 1.15 parts of ammonium dihydrogen phosphate 10 μm powder were weighed in molar ratio and added into a ball mill, and ball milled for 12 hours to obtain a mixed material, wherein the particle size of the mixed material was 700 nm;

[0056] The mixed material was placed in a box-type heating furnace, in an air atmosphere, and heated to 900°C at a rate of 3°C / min, kept at that temperature for 15 hours, and then cooled to room temperature to obtain a precursor;

[0057] The precursor is first crushed by a jaw crusher and a roller crusher, and then crushed into powder with a particle size of 5 μm by an impact crusher to obtain a micron-sized NASICON structure lithium-ion solid electrolyte material with a chemical formula of Li3Zr2Si2PO 12 .

[0058] The NASICON structure lithium ion solid electrolyte material Li3Zr2Si2PO prepared in this example 12 The XRD pattern of Figure 2 As shown, there are characteristic peaks at 20.0°, 27.0°, 35.6°, 43.8°, and 53.5°.

[0059] The NASICON structure lithium ion solid electrolyte material Li3Zr2Si2PO prepared in this example 12 Volume particle size distribution curve is as follows Figure 3 As shown, the average particle size D50 is 5 μm.

[0060] Example 2

[0061] This embodiment provides a method for preparing a NASICON structure lithium-ion solid electrolyte material.

[0062] The specific steps are as follows:

[0063] 3.55 parts of lithium hydroxide 5 μm powder, 1.86 parts of zirconium dioxide 3 μm powder, 1.92 parts of silicon dioxide powder and 1.15 parts of ammonium phosphate 12 μm powder were weighed in molar ratio and added into a ball mill, and deionized water was added, and ball milled for 8 hours to obtain a mixed material, the particle size of the mixed material was about 500 nm;

[0064] After drying the mixed material, place it in a tubular heating furnace, heat it to 860°C at a rate of 1°C / min, keep it at that temperature for 15 hours, and then cool it to room temperature to obtain a precursor;

[0065] The precursor was initially crushed by a jaw crusher and a roller crusher, and then graded and crushed into a powder with a particle size of 3 μm by a flat air flow mill to obtain a micron-sized NASICON structure lithium-ion solid electrolyte material with a chemical formula of Li 3.48 Zr 1.86 Si 1.92 P 1.08 O 12 .

[0066] The NASICON structure lithium ion solid electrolyte material Li prepared in this example 3.48 Zr 1.86 Si 1.92 P 1.08 O 12 The XRD pattern of Figure 4 As shown, there are characteristic peaks at 20.0°, 27.0°, 35.6°, 43.8°, and 53.5°.

[0067] The NASICON structure lithium ion solid electrolyte material Li prepared in this example 3.48 Zr 1.86 Si 1.92 P 1.08 O 12 Volume particle size distribution curve is as follows Figure 5 As shown, the average particle size D50 is 3 μm.

[0068] Example 3

[0069] This embodiment provides a method for preparing a NASICON structure lithium-ion solid electrolyte material.

[0070] The specific steps are as follows:

[0071] 3.2 parts of lithium hydroxide 5 μm powder, 2 parts of zirconium hydroxide 4 μm powder, 2.15 parts of silicon dioxide powder and 0.45 parts of phosphorus pentoxide 10 μm powder were weighed in molar ratio into a ball mill, and anhydrous ethanol was added, and ball milled for 6 hours to obtain a mixed material, wherein the particle size of the mixed material is 900 nm;

[0072] After drying the mixed material, place it in a tubular heating furnace, heat it to 950°C at a rate of 5°C / min, keep it at that temperature for 12 hours, and then cool it to room temperature to obtain a precursor;

[0073] The precursor was initially crushed by a jaw crusher and a roller crusher, and then graded and crushed into a powder with a particle size of 3 μm by a flat air flow mill to obtain a micron-sized NASICON structure lithium-ion solid electrolyte material with a chemical formula of Li 3.15 Zr2Si 2.15 P 0.85 O 12 .

[0074] The NASICON structure lithium ion solid electrolyte material Li prepared in this example 3.15 Zr2Si 2.15 P 0.85 O 12 The XRD pattern of Figure 6 As shown, there are characteristic peaks at 20.0°, 27.0°, 35.6°, 43.8°, and 53.5°.

[0075] The NASICON structure lithium ion solid electrolyte material Li prepared in this example 3.15 Zr2Si 2.15 P 0.85 O 12 The volume particle size distribution curve is as follows Figure 7 As shown, the average particle size D50 is 3 μm.

[0076] Example 4

[0077] This embodiment provides a method for preparing a NASICON structure lithium-ion solid electrolyte material.

[0078] The specific steps are as follows:

[0079] 3.6 parts of lithium hydroxide 5 μm powder, 1.9 parts of zirconium hydroxide 4 μm powder, 2.15 parts of silicon dioxide powder and 0.45 parts of phosphorus pentoxide 10 μm powder were weighed in molar ratio and added into a ball mill, and anhydrous ethanol was added, and the mixture was ball milled for 6 hours, and the particle size of the mixture was 900 nm;

[0080] The mixed material was dried and placed in a tubular heating furnace, heated to 1000°C at a rate of 8°C / min, kept at that temperature for 10 hours, and then cooled to room temperature to obtain a precursor;

[0081] The precursor was initially crushed by a jaw crusher and a roller crusher, and then crushed and graded into 16 μm powder by a flat air flow mill to obtain a micron-sized solid electrolyte material with a chemical formula of Li 3.55 Zr 1.9 Si 2.15 P 0.85 O 12 .

[0082] The NASICON structure lithium ion solid electrolyte material provided by the present invention contains stable zirconium and silicon elements. Compared with other solid electrolytes, when it is used as an electrolyte layer in a lithium ion battery, its chemical properties are more stable during the battery charging and discharging process, and it has the advantages of not reacting with positive and negative electrode materials and having good compatibility with positive and negative electrode materials. The preparation method of the NASICON structure lithium ion solid electrolyte material provided by the embodiment of the present invention is a high-temperature solid phase method, which has the advantages of easy availability of raw materials, low cost, simple preparation method, and easy industrial mass production.

[0083] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A NASICON structure lithium ion solid electrolyte material, characterized in that: The chemical formula of the NASICON structure lithium ion solid electrolyte material is Li (x-4y+9) Zr y Si x P (3-x) O 12 ; 0<x<3, 1≤y<2; The particle size of the NASICON structure lithium ion solid electrolyte material is between 500nm and 50μm; The NASICON structure lithium ion solid electrolyte material is obtained by a high temperature solid phase method; The high-temperature solid phase method is specifically as follows: the NASICON structure lithium ion solid electrolyte is obtained by mixing the raw materials uniformly and placing them in a high-temperature treatment device at a heating rate of 0.5°C / min-12°C / min to 900°C-1300°C for heat treatment, and then undergoing graded crushing treatment; The NASICON structure lithium ion solid electrolyte material is used in the separator of the lithium battery.

2. A method for preparing the NASICON structure lithium ion solid electrolyte material according to claim 1, characterized in that: The preparation method is a high temperature solid phase method, comprising: Weigh the raw materials in proportion, and mix the raw materials evenly by dry mixing or wet mixing to obtain a mixed material; placing the mixed material in a high temperature treatment device for heat treatment to obtain a precursor; The precursor is subjected to graded crushing treatment to obtain NASICON structure lithium ion solid electrolyte material with a particle size between 500nm-50μm; The chemical formula of the NASICON structure lithium ion solid electrolyte material is Li (x-4y+9) Zr y Si x P (3-x) O 12 , where 0<x<3, 1≤y<2.

3. The preparation method according to claim 2, characterized in that: The raw materials include: lithium-containing compounds, zirconium-containing compounds, silicon-containing compounds and phosphorus-containing compounds; The lithium-containing compound includes: one or more of lithium carbonate, lithium hydroxide, lithium oxide or lithium phosphate; the particle size of the lithium-containing compound particles is between 20nm-50μm; The zirconium-containing compound includes: one or more of zirconium oxide, zirconium hydroxide, zirconium silicate or zirconium hydrogen phosphate; the particle size of the zirconium-containing compound particles is between 20nm-50μm; The silicon-containing compound includes: silicon dioxide and / or silicon monoxide; the particle size of the silicon-containing compound particles is between 20nm-50μm; The phosphorus-containing compound comprises: one or more of lithium phosphate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphorus pentoxide; the particle size of the phosphorus-containing compound particles is between 20nm-50μm.

4. The preparation method according to claim 2, characterized in that: The dry mixing includes: mixing using a ball mill, mixing using a double motion mixer, or mixing using a high-speed mixer; The wet mixing includes: ball milling mixing, sand milling mixing or dispersion mixing.

5. The preparation method according to claim 2, characterized in that: The heat treatment equipment includes: a box furnace, a tube furnace, a track kiln, a rotary kiln or a push plate kiln.

6. The preparation method according to claim 2, characterized in that: The heat treatment comprises: heating to 900°C-1300°C at a heating rate of 0.5°C / min-12°C / min, keeping the temperature for 5 hours-30 hours, and then naturally cooling to room temperature.

7. The preparation method according to claim 2, characterized in that: The equipment for the graded crushing treatment includes: a jaw crusher, a cone crusher, an impact crusher, a hammer crusher, a roller crusher, a flat air flow mill, a fluidized bed air flow mill, a circulating air flow mill, an impact crusher, an expansion crusher, a ball mill, a high-speed rotating projectile mill or a high-speed rotating impact mill.

8. A diaphragm, characterized in that: The separator comprises the NASICON structure lithium ion solid electrolyte material as claimed in claim 1 above.

9. A lithium battery, characterized in that: The lithium battery comprises the separator according to claim 8 above.